Metabolic and physico-chemical urolithiasis parameters in the first morning urine - Šerić, Vatroslav, medicinski biokemičar; Dutour Sikirić, Maja; Mihaljević, Ivan, liječnik; Tucak-Zorić, Sandra; Bilić-Ćurčić, Ines; Babić-Ivančić, Vesna (2009)
Summary: The 24-hour urine is golden standard for metabolic assessment of stone formers. However, due to the difficulties in collecting almost 1/3 of the samples can not be used for the analysis. Therefore, we analyzed first morning urine and calculated different risk indexes in order to asses possibility of using it in determining urolithiasis risk. Subjects were divided into 4 groups: male patients (n=31, age 18–64), female patients (n=31, age 25–63), male controls (n=16, age 25–64) and female controls (n=19, age 21–65). First morning urine pH, concentrations of calcium, magnesium, phosphate, sodium, potassium, chloride, citrate, urate, oxalate, creatinine and glycosaminoglycans were determined. Based on them, ionic concentrations and activity products of calcium oxalate and phosphate were calculated by EQUIL 2. In addition, different risk indices were calculated. The results showed that both patients and control groups had metabolic disorders, but the frequencies of occurrence were statistically independent. Significant difference in concentration of urinary constituents between corresponding patient and control groups was observed only for glycosaminoglycans in female subjects. Ca/Cit ratio and Baggio index could differentiate between both corresponding patients and control groups. The results indicate that interplay between stone formation inhibitors and promotors is responsible for urinary stone formation and that the first morning urine could be used in assessing urolithiasis risk and its prevention
Bibliografija: 44 jed
Keywords: Urolitijaza -- Urin -- Metabolički poremećaj